2016
DOI: 10.1002/cnma.201600142
|View full text |Cite
|
Sign up to set email alerts
|

Color Tunable Ultrathin Films Capable of Healing Multiple Scratches

Abstract: Healable films with structural color are highly desirable and have a variety of potential applications. However, combining structural color with self-healing properties to obtain new functional materials is a big challenge in current research. Herein, we present the first example of a color tunable, ultrathin film that can self-heal in response to external mechanical abrasion. It is designed based on intermolecular hydrogen bonding interaction; the synthetic strategy involves spin-coating of poly(acrylic acid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…24 Comparative observation of the black line and red line with the blue line (CS/ CMC multilayer polyelectrolyte coating) revealed that it can be found that the absorption peaks of the amino and carboxyl groups shied, which indicates that CS and CMC interact through hydrogen bonding. 25 The hydrogen bonding can undergo a reversible "break-rebuild" process under certain stimulation conditions, which is suitable for the designing of new stimulus-response materials. Recently, a lot of new functional materials with self-healing property were constructed through hydrogen bonding; for example, Sun et al have successfully constructed a coating material with excellent selfhealing performance based on the hydrogen bonding between bPEI and PAA.…”
Section: Resultsmentioning
confidence: 99%
“…24 Comparative observation of the black line and red line with the blue line (CS/ CMC multilayer polyelectrolyte coating) revealed that it can be found that the absorption peaks of the amino and carboxyl groups shied, which indicates that CS and CMC interact through hydrogen bonding. 25 The hydrogen bonding can undergo a reversible "break-rebuild" process under certain stimulation conditions, which is suitable for the designing of new stimulus-response materials. Recently, a lot of new functional materials with self-healing property were constructed through hydrogen bonding; for example, Sun et al have successfully constructed a coating material with excellent selfhealing performance based on the hydrogen bonding between bPEI and PAA.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 When being applied in daily life, colloidal PCs are likely to be handled via physical mechanisms, which in turn can bring the possibility of damage to the delicate periodic nanostructures, leading to the failure of the optical and/or structural properties. 37,38 Therefore, improving the mechanical strength of colloidal PC materials has been one of the critical aspects to ensure the durability and stability of PCs. To this end, several strategies have been employed for the construction of mechanically robust colloidal PCs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this versatility, LbL films have been designed to incorporate responsive polymers to respond to a wide range of external changes in pH, ionic strength, temperature, solvation, light, enzyme, and electrochemical and mechanical loads . There are, in fact, three reasons LbL assembly is considered an effective way to produce nanofilms that could generate tunable structural colors: i) The stepwise deposition allows precise control of film thickness in the length scale of visible wavelength (hundreds of nanometers); ii) postmodification of the chemical compositions of LbL film offers the possibility for surface patterning, and iii) the dynamic response of LbL films provides the potential to achieve real‐time tenability …”
Section: Introductionmentioning
confidence: 99%